PERAN KEPALA SEKOLAH SEBAGAI MOTIVATOR DALAM UPAYA MENINGKATKAN KINERJA GURU DI SMP NEGERI 24 KOTA JAMBI - Fairus Rizky; Denny Denmar; Yudo Handoko (STKIP Pesisir Selatan, 2026)
The principal plays a central role in improving teacher performance through motivation, guidance, and the creation of a conducive work environment. However, several issues arise, such as inconsistent use of E-Performance technology and differences in teacher readiness to improve their professionalism, which remain obstacles. This study aims to describe the experiences of the principal as a motivator at SMP Negeri 24 Jambi City in improving teacher performance, teacher performance at SMP Negeri 24 Jambi City, and supporting and inhibiting factors from a managerial and organizational perspective. The method used in this study is qualitative phenomenology by collecting data from in-depth interviews with the principal, vice principal, teachers, and students, which were then confirmed by data triangulation. The results of the study indicate that the principal plays a role as a motivator through providing psychological motivation, being a role model for the principal, implementing academic supervision, and implementing teacher professional development activities. These roles have an impact on improving teacher performance in systematically planning and preparing learning materials, although the use of learning outcome evaluation has not been carried out consistently.